ISLAMIC ORGANIZATIONS IN NORTH SUMATRA: The Politics of Initial Establishment and Later Development (JOURNAL OF INDONESIAN ISLAM, 2016)
This paper describes the politics of initial establishment and later development of four Islamic organizations in North Sumatra: Muhammadiyah, Al Jam`iatul Washliyah, Nahdlatul Ulama, and Al Ittihadiyah. It particularly focuses on the historical evolution and dynamics of these four Islamic organizations. As a subject of analysis, it, for the most part, assesses the aspects of ethnicity, religious doctrine, educational institution, and political aspiration reflected by these organizations in that area. The paper shows that these four organizations have contributed much to the progress of the Islamic community in this region.